1989
DOI: 10.1111/j.1365-2621.1989.tb04700.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pretreatment on the Cooking Time of the African Yam Bean (Sphenostylis sternocarpa)

Abstract: The effect of soaking in tap water, 1% potash, and 4% sodium chloride for different periods on the cooking time of African Yam Bean was studied. The results showed that 12 hr soaking was adequate for the beans to reach maximum hydration, and that pretreatment of the beans before cooking appreciably influenced the overall cooking time. Cooking after pretreatment for 12 hr in 1% potash or in 4% sodium chloride reduced the normal cooking time by 50%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…A higher moisture content of the soaked beans reduces the cooking time [9]. Njoku et al [10] reported that soaking African yam bean in 4% sodium chloride solution reduced cooking time by 50%. Apart from reducing cooking time, soaking causes reductions in the levels of some anti-nutritional factors.…”
Section: Introductionmentioning
confidence: 98%
“…A higher moisture content of the soaked beans reduces the cooking time [9]. Njoku et al [10] reported that soaking African yam bean in 4% sodium chloride solution reduced cooking time by 50%. Apart from reducing cooking time, soaking causes reductions in the levels of some anti-nutritional factors.…”
Section: Introductionmentioning
confidence: 98%
“…Amino acid analyses indicate that the lysine and methionine levels in the protein are equal to or better than, those of soybeans. The characteristic problem of the hard‐to‐cook phenomena, which has hindered the extensive use of YB, has been substantially reduced through selected treatments (Njoku et al . 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The seeds are hard and preparing the meal by traditional processing methods can take up to 24 h. This often precludes the seeds from being acceptable, especially in this era of urbanization. The hard‐to‐work phenomenon has been studied by Njoku et al . (1989), who reported that the cooking time can be reduced by 50% through precooking treatments such as steeping the seeds in 1% w/v potash or 4% w/v NaCl for 12 h.…”
Section: Introductionmentioning
confidence: 99%